Normans in the Adriatic: Reliquary of Saint Christopher at the island of Rab (Croatia) as the Site of the Collective Memory - Munk, Ana (2013)
The presentation focused on the political aspects of the martyrdom of Saint Chrystopher depicted on the 12th century reliquary in Rab cathedral in relation to the 14th century text describing the attack on the island of Rab and the role of Saint Chrystopher's relics in the city defense.
ENG